Pulsed electromagnetic fields preconditioned extracellular vesicles derived from mesenchymal stromal cells prevents necroptosis of osteoblasts in osteonecrosis of the femoral head rats - Xiang, Xiao-Na; Zhang, Jiang-Yin; Wang, Xiang-Xiu; He, Hong-Chen; He, Cheng-Qi (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundOsteonecrosis of the femoral head (ONFH) is a refractory orthopedic disease in which steroids may induce bone cell necroptosis. Extracellular vesicles derived from bone marrow mesenchymal stromal cells (BMSC-EVs) are recognized as novel therapies to improve ONFH. Pulsed electromagnetic fields (PEMFs) increase the paracrine activity of BMSCs. Nonetheless, the effect and mechanism of PEMFs preconditioned BMSC-EVs (BMSC-EVsPEMFs) for treating ONFH are unclear.MethodsThe BMSC-EVsPEMFs with different magnetic amplitudes were incubated with dexamethasone-induced MC3T3-E1 cells and the osteogenic differentiation and necroptosis were observed. Furthermore, RNA sequencing of MC3T3-E1 cells incubated with incubated with PEMFs of a specific amplitude or without PEMFs was conducted to identify potential mechanisms involved. Reverse transcription‒quantitative polymerase chain reaction (RT-qPCR), immunofluorescence and Western blotting were performed to detect necroptosis-related pathways. SD rats receiving steroid injections were randomly assigned to receive PBS, BMSC-EVs or BMSC-EVsPEMFs therapy. Micro-CT scan, histological, and immunohistochemical analyses were used to evaluate the therapeutic effects on bone formation and necroptosis of the femoral head in ONFH animals.ResultsThe characteristics of the BMSC-EVsPEMFs were similar to those of the BMSC-EVs. In vitro, co-culture of osteoblasts and PEMFs with 3 millitesla (mT) amplitude preconditioned BMSC-EVs (BMSC-EVsPEMFs (3 mT) promoted osteogenic differentiation and inhibited cell death. The results of RNA sequencing revealed that the expression of Ripk3 was significantly lower in the BMSC-EVsPEMFs (3 mT) group than in the BMSC-EVs group. RT-qPCR, immunofluorescence and Western blotting revealed that the expression of necroptosis-related molecules (RIPK1, RIPK3, and MLKL) was suppressed in BMSC-EVsPEMFs (3 mT) group (p < 0.05). In vivo, the BMSC-EVsPEMFs (3 mT) group presented better bone morphology of the femoral head via micro-CT, with a lower protein expression of MLKL and a higher expression of RUNX2 (p < 0.05) at 2 weeks, while lower expressions of RIPK1 and RIPK3, and higher levels of RUNX2 and OCN (p < 0.05) at the femoral head at 6 weeks after injection than did the BMSCs-EVs group.ConclusionPEMFs with 3 mT amplitude preconditioned BMSC-EVs could promote bone formation by inhibiting osteoblasts necroptosis via Ripk1–Ripk3–Mlkl signaling in ONFH.